2011
DOI: 10.1371/journal.pone.0027291
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease and Non-Demented High Pathology Control Nonagenarians: Comparing and Contrasting the Biochemistry of Cognitively Successful Aging

Abstract: The amyloid cascade hypothesis provides an economical mechanistic explanation for Alzheimer's disease (AD) dementia and correlated neuropathology. However, some nonagenarian individuals (high pathology controls, HPC) remain cognitively intact while enduring high amyloid plaque loads for decades. If amyloid accumulation is the prime instigator of neurotoxicity and dementia, specific protective mechanisms must enable these HPC to evade cognitive decline. We evaluated the neuropathological and biochemical differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 121 publications
8
81
0
Order By: Relevance
“…46 These findings are in accordance with results from several transgenic mouse lines that express human versions of AD-inducing mutated genes, which show no evidence of strong neuroinflammatory responses nor widespread progressive neuronal cell death. 49 Of further interest, Aβ 1-42 levels in the brains of high-pathology controls were much higher than those in the brains of aged-matched patients with AD, 50 in agreement with a controversial proposal that Aβ 1-42 may be protective rather than toxic, 51 as further discussed below. In addition, PET imaging studies revealed that cognitive status in patients with AD is inversely correlated with microglial activation, but not Aβ load.…”
Section: Inflammation-a Key Playersupporting
confidence: 77%
“…46 These findings are in accordance with results from several transgenic mouse lines that express human versions of AD-inducing mutated genes, which show no evidence of strong neuroinflammatory responses nor widespread progressive neuronal cell death. 49 Of further interest, Aβ 1-42 levels in the brains of high-pathology controls were much higher than those in the brains of aged-matched patients with AD, 50 in agreement with a controversial proposal that Aβ 1-42 may be protective rather than toxic, 51 as further discussed below. In addition, PET imaging studies revealed that cognitive status in patients with AD is inversely correlated with microglial activation, but not Aβ load.…”
Section: Inflammation-a Key Playersupporting
confidence: 77%
“…Since the identified SNPs are located mainly in CpG islands within the Reelin promoter (Chen et al, 2002), shown to undergo epigenetic modifications as a part of regulatory mechanism of LTP (Levenson et al, 2008, Sui et al, 2012, it would be of highest relevance to further confirm (Kramer et al, 2011) and to check if these SNPs (Seripa et al, 2008) are correlated with a significant increase or decrease of Reelin levels, respectively. In line with Reelin's role in suppressing NFT formation, it is important to mention that elderly people with high AD pathology but no dementia, the so-called high pathology controls (Kramer et al, 2011, Krstic andKnuesel, 2013) differ from AD patients in the amount of NFT load in the frontal cortex (Maarouf et al, 2011). …”
Section: And Promotesmentioning
confidence: 94%
“…It has been demonstrated that Aβ1-40 levels were 20-fold higher in AD brains compared to PA brains, whereas Aβ1-42 levels were only twofold higher [42]. Overall, several studies suggested quantitative and qualitative differences in the amyloid deposits between PA and AD brains [43]. It can be concluded that a wide spectrum of harmful effects of Aβ species, peptides, oligomers or plaques coincides with the disturbed presenilin signalling.…”
Section: Presenilin Substrate App and Production Of Toxic β-Amyloid Pmentioning
confidence: 98%